A moderate decrease of plastid aldolase activity inhibits photosynthesis, alters the levels of sugars and starch, and inhibits growth of potato plants - Sonnewald, Uwe; et al. (Plant Journal, 1998)
Antisense expression of a full length cDNA encoding plastid aldolase led to decreased expression of aldolase at the transcript and protein level in several 'antisense' potato transformants. To quantify the inhibition, activity was compared in corresponding leaves down a plant and in plants of different ages. Aldolase activity was decreased by 32-43%, 56-71%, 79-83% and 91-97% in A-70, A-3, A-51 and A-2. Separation on a Q-Sepharose-FF column showed the decrease was due to inhibition of plastid aldolase. The transformants showed a small increase of Rubisco activity, a small decrease of phosphoribulokinase activity, and larger but subproportional decreases of sedoheptulose-1,7-biphosphatase and plastid fructose-1,6-bisphosphatase activity. Ambient photosynthesis was inhibited by 10%, 40%, 66% and 85% in A-70, A-3, A-51 and A-2. The transformants contained increased triose phosphates, and very low ribulose-1,5-bisphosphate and glycerate-3-phosphate. Chlorophyll fluorescence indicated that photosystem II was more reduced and thylakoid energization was increased. Starch synthesis was decreased by 16% and 36% in A-70 and A-3, whereas sucrose synthesis was less strongly inhibited. Plant growth was not significantly altered in A-70, was decreased by 41% in A-3, and was severely inhibited in plants with under 20% of wild-type aldolase activity. Although plastid aldolase catalyses a readily reversible reaction, possesses no known regulatory properties, and would appear irrelevant for the control of metabolism and growth, small changes in its activity have marked consequences for photosynthesis, carbon partitioning and growth.